Creep Characteristics of Different Saturated States of Red Sandstone after Freeze-Thaw Cycles - Yongxin Che; Yongjun Song; Jianxi Ren; Jiaxing Chen; Xixi Guo; Hao Tan; Mengling Hu (Geofluids)
To investigate the creep mechanical characteristics of rocks in different saturated states after freeze-thaw cycles, samples with different saturations (30%, 50%, 70%, 90%, and 100%) were selected for nuclear magnetic resonance (NMR), scanning electron microscopy (SEM), and uniaxial compression creep tests. The internal microscopic damage of the rock sample and mechanical characteristics under long-term loading are analyzed after the action of freeze-thaw cycles. The test results show that, as the saturation increases, the T2 spectrum distribution shifts to the right. The spectrum area gradually increases as the porosity increases. The critical saturation of freeze-thaw damage occurs when the saturation increases from 70% to 90%. It can be seen from the SEM image that the number of pores inside the rock samples gradually increases with increases in saturation, leading to the appearance of cracks. Under long-term loading, the saturation has a significant influence on the time-efficiency characteristics of sandstone freeze-thaw. As the saturation increases, the creep deformation gradually increases. After reaching 70%, the axial creep strain increases significantly. The rate of creep is accelerated, the creep failure stress is reduced, and the creep time under the last level of stress is significantly increased. A modified viscous-plastic body is connected in series to the basic Burgers model, the freeze-thaw-damage viscous element is introduced, and the creep parameters are fitted using test data. The results will provide a reference for long-term antifreeze design for rock engineering in cold areas.